Sea cucumber phytochemical compounds have the potential to reduce TNF-a levels after exercise - Novadri Ayubi; Sri Gusti Handayani; Afifan Yulfadinata; Anton Komaini; Junian Cahyanto Wibawa; Ainun Zulfikar Rizki; Alvin Afandi; Muhammad Firman Halip (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Increased levels of TNF-a in the blood after exercise can cause muscle pain.